New insights into the targeting of a subset of tail-anchored proteins to the outer mitochondrial membrane - Marty, Naomi J.; Teresinski, Howard J.; Hwang, Yeen Ting; Clendening, Eric A.; Gidda, Satinder K.; Sliwinska, Elwira; Zhang, Daiyuan; Miernyk, Ján A.; Brito, Glauber C.; Andrews, David W.; Dyer, John M.; Mullen, Robert T. (Frontiers in Plant Science, 2014)
Tail-anchored (TA) proteins are a unique class of functionally diverse membrane proteins defined by their single C-terminal membrane-spanning domain and their ability to insert post-translationally into specific organelles with an Ncytoplasm-Corganelle interior orientation. The molecular mechanisms by which TA proteins are sorted to the proper organelles are not well understood. Herein we present results indicating that a dibasic targeting motif (i.e., -R-R/K/H-XX≠E) identified previously in the C terminus of the mitochondrial isoform of the TA protein cytochrome b5, also exists in many other A. thaliana outer mitochondrial membrane (OMM)-TA proteins. This motif is conspicuously absent, however, in all but one of the TA protein subunits of the translocon at the outer membrane of mitochondria (TOM), suggesting that these two groups of proteins utilize distinct biogenetic pathways. Consistent with this premise, we show that the TA sequences of the dibasic-containing proteins are both necessary and sufficient for targeting to mitochondria, and are interchangeable, while the TA regions of TOM proteins lacking a dibasic motif are necessary, but not sufficient for localization, and cannot be functionally exchanged. We also present results from a comprehensive mutational analysis of the dibasic motif and surrounding sequences that not only greatly expands the functional definition and context-dependent properties of this targeting signal, but also led to the identification of other novel putative OMM-TA proteins. Collectively, these results provide important insight to the complexity of the targeting pathways involved in the biogenesis of OMM-TA proteins and help define a consensus targeting motif that is utilized by at least a subset of these proteins.